Aflibercept for Retinopathy of Prematurity A Systematic Review and Meta-Analysis - Chen, Po-Yu Jay (Ophthalmic surgery, lasers & imaging retina, 2021)
BACKGROUND AND OBJECTIVE: To determine the effectiveness of aflibercept in retinopathy of prematurity (ROP)